Kelios rytų aukštaičių širvintiškių ir pietų panevėžiškių tarmių vokalizmo ypatybės - Markevičius, Valdimantas (Baltistica, 2002)
SOME PECULIARITIES OF THE VOCALISM OF EAST AUKŠTAITISH SUBDIALECTS OF ŠIRVINTIŠKIAI AND SOUTH PANEVĖŽIŠKIAI According to the official scientific division of Lithuanian dialects, the distinctive feature separating the subdialects of Širvintiškiai and South Panevėžiškiaiis different pronunciation of short vowels in word endings. Speakers of the Širvintiškiai subdialect are said to retain and pronounce differently all the four vowels (a, e, i, u) that are possible in this position, while speakers of the South Panevėžiškiai subdialect are said to merge all of them into one sound, i. e. the reduced vowel ʋ (following non-palatalised consonants) or ι(following palatalised consonants). Therefore, the Širvintiškiai subdialect possesses the vowels ǎ and ě in word endings, while the Panevėžiškiai subdialect does not have them. Yet one should not forget that the Širvintiškiai subdialect does not possess ǎ and ě in numerous word forms, either, e. g., vil̃.kus, vil̃.kʋs, or vil̃.kыs ‘wolf’, and in the territory around the Gelvonai settlement there are also forms like bé̤˙gы ‘is running’, pí.lnы ‘plenty’ and kúosы‘jackdaw’. The pronunciation of the respective vowels is very similar in word endings of the South Panevėžiškiaisubdialect: bé̤˙gʋ, pí.lnʋ, kúosʋ. On the other hand, the Panevėžiškiai subdialect speakers have some word forms where the vowels ǎ and ě are pronounced in word final positions. This is especially characteristic of the vocative case: kàte, ma̾˙mα. For the above-mentioned reasons, different pronunciation of the Baltic vowel ā in unstressed syllables (the žalininkai feature) would be a better feature for distinguishing the two subdialects. Speakers Of the Širvintiškiai subdialect have the žalininkai feature in their speech, e. g., žalí˙te ‘grass’. Panevėžiškiai subdialect speakers, on the contrary, have no such feature. Cf. the word žuli̾˙te in the South Panevėžiškiai subdialect and its counterpart in the North Panevėžiškiaisubdialect, žọlí˙te . Contemporary Lithuanian dialectology deviates a little from the real situation in indicating the territorial limits of the Širvintiškiai subdialect. The present article is an attempt to correct this inaccuracy.